Techno-economic analysis of bioethanol production from rice straw by liquid-state fermentation - Hidayata M.H.M.; Salleh S.F.; Riayatsyahb T.M.I.; Aditiyac H.B.; Mahliaa T.M.I.; Shamsuddina A.H. (Institute of Physics Publishing, 2023)
Cost benefit analysis; Costs; Economic analysis; Ethanol; Agricultural sector; Alternative energy source; Bio-ethanol production; Economically viable; Lignocellulosic biomass; Liquid state fermentation; Malaysian governments; Techno-Economic analysis; Bioethanol; biofuel; commercialization; economic analysis; energy use; fermentation; liquid; phytomass; potential energy; renewable resource; rice; straw; technical efficiency; Malaysia